Medinių daugiasluoksnių armuotų sijų standumo tyrimai veikiant trumpalaikėms ir ilgalaikėms skersinėms jėgoms - Čechavičius, Rimantas (Journal of Civil Engineering and Management, 1998)
Investigations into the deflection of reinforced multi-layer prestressed timber beams under short- and long-time shearThe article continues a series of papers dealing with the investigations into the strength of multi-layer beams under the action of shear [1, 2]. The results of research on the stiffness of timber reinforced beams are presented. As a result of experiments the authorial certificates of five inventions were obtained. One of them is the certificate of the invention SU 1091047 A, G 01 M5/00 “The equipment of experiment of building constructions” [3]; it is also described in the paper. The objective of the experiments was to check the new method of increasing load-bearing capacity of timber multi-layer beams: prestress of separate wooden layers across the axis of the element, described in the above-mentioned papers [1, 2]. The results of investigations in stiffness of 28 timber reinforced beams of different cross-section and the way of manufacture under the action of shear are given in the paper. Sixteen beams were tested by static short-time loading and the rest twelve by static long-time loading. All beams failed because of shear. It was determined that deflections of timber reinforced beams under short-time design loads independently on the constructions are much larger (in average 1.48–1.88 times) than those calculated according to the running standards. Because of insufficient evaluation of the shear influence on the deflections the author offers to make it more precise with the help of coefficient kc in the formula (1): for timber reinforced beams without prestressing kc = 2.75, for multi-layer beams with prestressing kc = 1.75. Deflections of timber reinforced beams, of multi-layer beams with prestressing among them at the time of failure under short-time loading are in average 4.75–5.08 times and under long-time loading – 5.59–6.75 times bigger than those calculated according to the codes of practice for the same beams under design loads. Deflections at the time of timber reinforced beams, that have not failed because of longtime loading and have been tested by static short-time loading were smaller than those fixed during a long-time testing under much smaller (0.50 ÷ 0.78 Vu,t) loads, but the deflections of the same beams under design loads are close to those (f et /f e = 0.97 ÷ 0.99) calculated according to the codes of practice. The efficiency of the experiments of building structures may be significantly enlarged when using the test equipment, presented in the invention SU 1091047 [3], the formula of which is as follows: the equipment of building structure test consists of the beam with support, loading and measuring devices and differs in setting of the structure loading devices on different sides of the beam for increasing the effect of the experiment (Fig. 7).Article in Lithuanian.First Published Online: 26 Jul 2012